Kunstenaars Kennen. (Leuven : Stadsbestuur Leuven, 1969)
Aubroeck, Karel ; De Sutter, Jules ; Malfait, Hubert ; Van Damme, Suzanne ; Vanderlick, Armand ; Vinck, Jozef ; Wolfens, Henri-Victor
Kunstenaars Kennen, Stadhuis Leuven, 1-22 februari 1969
boek